2015
DOI: 10.5116/ijme.5557.25f9
|View full text |Cite
|
Sign up to set email alerts
|

Educational climate perception by preclinical and clinical medical students in five Spanish medical schools

Abstract: ObjectivesThe purpose of this study was to investigate student's perceptions of Educational Climate (EC) in Spanish medical schools, comparing various aspects of EC between the 2nd (preclinical) and the 4th (clinical) years to detect strengths and weaknesses in the on-going curricular reform. MethodsThis study utilized a cross-sectional design and employed the Spanish version of the "Dundee Ready Education Environment Measure" (DREEM). The survey involved 894 2nd year students and 619 4th year students from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 28 publications
7
38
0
4
Order By: Relevance
“…Items asking about friends (number 15) and accommodation (number 46) got the highest scores. Similar results were reported in both national and foreign universities 4 , 16 . The presence of friendly relationships between the students reflects a healthy environment.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Items asking about friends (number 15) and accommodation (number 46) got the highest scores. Similar results were reported in both national and foreign universities 4 , 16 . The presence of friendly relationships between the students reflects a healthy environment.…”
Section: Discussionsupporting
confidence: 86%
“…The reported scores agree with the general conclusion that DREEM scores in traditional schools are generally less than 120 9 . Similar results in Europe showed the existence of several educational problems associated with the traditional curricula and the teaching methodologies 4 . In a recent systematic review, it has been concluded that the DREEM inventory is the most suitable tool for measuring the educational environment for undergraduate medical students 18 .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…A similar situation has been described in medical students in the case of skills for inter-professional collaborative work (Hojat et al 1999). Such differences disappear in the case of perception for the educational environment (Palés et al 2015) and the skills for lifelong medical learning (Wetzel et al 2010). Differences in the development of these elements as a function of age in studies with students have not been described either, although they have been described in studies with professionals that include a wider range of age (Hojat 2006).…”
Section: Jsapnc Jefferson Scale Of Attitudes Toward Physician-nurse Cmentioning
confidence: 99%